Analisis Arah Kebijakan Pemenuhan Hak Politik Pemilih Disabilitas Mental pada Pemilu Tahun 2024 - Mohamad Ihsan; Nadya Kharima (UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. The issue of fulfilling political rights for voters with mental disabilities in the 2019 general election still left many problems, ranging from the presence of the Constitutional Court's decision to the stigma of society towards voters with mental disabilities. With the decision from the Constitutional Court that allows people with mental disabilities to become voters, it actually causes a lot of disturbance to people with mental disabilities. Therefore, the authors are interested in seeing how the policy direction for fulfilling the political rights of voters with mental disabilities will be in the 2024 election. With a qualitative methodology that aims to reveal facts and provide an overview and phenomena that occur with literature study and interview techniques, it is expected to be able to provide an overview of the policy on fulfillment of the political rights of voters with mental disabilities as expected in the 2024 elections. Based on the findings that existing policies still need to be addressed in order to provide clearer definitions, mechanisms, and requirements for voters with mental disabilities. Access to information on the policy is also felt to be important for both mentally disabled voters and lower-level implementers in order to implement it properly.Keywords: Policy, Voters with Mental Disabilities, 2024 General Election. Abstrak. Persoalan pemenuhan hak politik bagi pemilih disabilitas mental pada pemilu tahun 2019 yang lalu masih menyisakan banyak persoalan, mulai dari hadirnya keputusan MK hingga stigma masyarakat terhadap pemilih disabilitas mental. Dengan keputusan MK yang memperbolehkan penyandang disabilitas mental menjadi pemilih justru banyak menimbulkan pengusikan terhadap penyandang disabilitas mental. Oleh karena itu, penulis tertarik untuk melihat bagaimana arah kebijakan pemenuhan hak politik pemilih disabilitas mental pada pemilu tahun 2024. Dengan metodologi kualitatif yang memiliki tujuan guna mengungkapkan fakta serta memberikan gambaran dan fenomena yang terjadi dengan teknik studi pustaka dan wawancara diharapkan mampu memberikan gambaran terhadap kebijakan pemenuhan hak politik pemilih disabilitas mental sesuai dengan yang diharapkan di pemilu tahun 2024. Berdasarkan temuan bahwa kebijakan yang sudah ada masih harus dibenahi agar dapat memberikan definisi, mekanisme serta syarat-syarat bagi pemilih disabilitas mental yang lebih jelas. Akses informasi terhadap kebijakan tersebut juga dirasakan penting baik bagi pemilih disabilitas mental maupun pelaksana tingkat bawah agar dapat mengimplementasikan secara baik.Kata Kunci: Kebijakan, Pemilih Disabilitas Mental, Pemilu 2024.